Decarbonising transport in Europe: Trends, goals, policies and passenger car scenarios. (March 2022) - Danielis, Romeo; Scorrano, Mariangela; Giansoldati, Marco
Abstract: The paper has two main goals: to draw a summary picture of the progress made towards transport decarbonisation in Europe, and to identify future developments concerning the 2020–2030 decade. The analysis is based on the 4th and 5th reports prepared by the Member States under the obligation Renewable Energy Directive (2009/28/EC) and on the National Energy and Climate Plans (NECPs) for the 2020–2030 decade, paying specific attention to the use of renewables in the transport sector. We find that the Member States rely on two strategies: increasing the production and use of biofuels, especially those produced by advanced materials, and supporting the diffusion of electric vehicles. Performing a scenario analysis capturing the planned policies and goals indicated in the NECPs, we estimate that the biofuel strategy can deliver a GHG reduction of up to 19 MtCO2eq (−3.6%), while the electrification strategy can deliver a GHG reduction up to 45 MtCO2eq (−8.3%). Jointly used, the GHG reduction could reach up to 64 MtCO2eq (−11.9%).